A case report of CHARGE syndrome caused by a de novo gene mutation - Yuan Zhang; Yu Lu; Xicui Long; Wenyu Xiong; Yuqing Liu (SAGE Open Medical Case Reports)
This article describes the case of a patient with CHARGE syndrome. The clinical data of the patient as well as the whole-genome sequencing results of the child and parents were retrospectively analyzed to determine the pathogenicity of the gene mutation. Genetic testing revealed a heterozygous mutation of the CHD7 gene NM_017780.4: C.4853G >A (P.TP1618ter) in the child, which was identified as a de novo pathogenic mutation. Through this case, we conclude that genetic testing is crucial for accurate diagnosis of deafness. Moreover, paying attention to hearing screening in childhood and strengthening the cognitive level of diagnosis and treatment of syndromic deafness in multiple disciplines can effectively realize early detection, early diagnosis, early intervention, and early rehabilitation of syndromic deafness.